Failure analysis of cavitation in a hydraulic loader. (August 2016) - Mo, Li; Yang, Qi; Yang, Yu; Zeng, Zhichun
Abstract: Cavitation is one of the major failure modes in hydraulic loaders. The failure mechanism is related to damage induced by cavitation at the working surface. Moreover, the vibrations caused by cavitation reduce the efficiency of the unit and lead to irregular output. To further explore the cavitation-induced failure mechanism in hydraulic loaders, a vapor/liquid two-phase flow numerical calculation method was used to obtain the radial distribution of water vapor volume fraction in the internal flow field with different structural parameters of a prototype hydraulic loader. This method was also used to predict the intensity of cavitation under different conditions. It was found that with an increase of the stator and rotor blade angle, blade number and blade thickness, the water vapor volume fraction and intensity of cavitation reduced; however, with an increase of the stator and rotor vortex pit depth, water vapor volume fraction and cavitation intensity increased. Moreover, the clearance of the assembly had little effect on cavitation. The results of the numerical simulation are in good agreement with the experimental observations, which verifies the reliability of the calculation method for cavitation failure analysis of a hydraulic loader and provides a good basis for structure optimization. Highlights: The hydraulic loader model studied in this paper is a novelty. The studies about the influence of fluid mechanical structure on cavitation are scarce. The results of cavitation numerical simulation are consistent with the experimental observations of cavitation failure.